Development of a Photoelectric Adjustment System With Extended Range for Fluorescence Immunochromatographic Assay Strip Readers - Huihuang Wu; Yueming Gao; Jiejie Yang; Mangi Vai; Min Du; Siohang Pun (IEEE Photonics Journal, 2021)
Fluorescence immunochromatographic assay (FICA) is a quantitative detection technique widely used in clinical diagnosis, environmental monitoring, and food safety. To deal with the limited applications caused by insufficient detection range, this paper proposes a photoelectric adjustment system suitable for FICA strip readers to expand its detection range. The photoelectric adjustment system is proposed based on the relationship between the excitation light intensity and the fluorescence intensity, which provides the optimal excitation light intensity and a stable baseline amplitude for the FICA strip reader. To verify the proposed system, it was applied to the strip reader we had previously developed. The results show that the linear detection range of the FICA strip reader was extended from 1.95-256 μg/mL to 1-1024 μg/mL after using the proposed method. At the same time, the accuracy of the FICA strip reader does not deteriorate and is in good comparisons with the conventional ESEQuant Lateral Flow Reader (with R2 > 0.9987). Therefore, the proposed photoelectric adjustment method and system can improve the detection range of the strip reader or other similar devices.